Occurrences et dénonciation des « idées reçues » dans la création nouvellesque de Guy de Maupassant - Anghel, Liliana (Romanica Silesiana, 2021)
In this essay I intend to show how Maupassant turned his short stories into a denouncement area of the ‘inherited ideas’, which mean commonly accepted ideas, such as those included by Flaubert in his Dictionary of inherited ideas. In this part of Maupassant’s literary work, the syntagm ‘inherited ideas’ acquires several different meanings, such as: some commonplace topics of the French bourgeoisie, the hasty taking up of fashionable words, attitudes, or cultural clichés, which one may come across in everyday life, the tendency of accepting as unchallenged some social, moral or religious prejudices, or foolish beliefs and unjust statements, authoritatively uttered by ordinary people. I’ll also emphasize the manner Maupassant treated the ‘inherited ideas’ by his ironical hints and the narrator’s affective implication, in spite of his seeming impassibility.